Emergent Comprehension and its Significance in Early Years - Bahuguna, Pooja (JOURNAL OF INDIAN EDUCATION, 2017)
Various contemporary reading theories favour the view that literacy is developmental in nature. Hence, children’s early experiences of reading and comprehension are equally valuable in the development of reading comprehension before they begin going to schools. The present paper builds this view by reviewing and reflecting on various related researches and practice relation. The paper also discusses the quality of early reading and comprehension practices in the Indian context in the light of related theories.